The impact of tranexamic acid on mortality in injured patients with hyperfibrinolysis. Issue 5 (May 2015) - Harvin, John A.; Peirce, Charles A.; Mims, Mark M.; Hudson, Jessica A.; Podbielski, Jeanette M.; Wade, Charles E.; Holcomb, John B.; Cotton, Bryan A.
<x xml:space="preserve">Abstract</x> BACKGROUND In 2011, supported by data from two separate trauma centers, we implemented a protocol to administer tranexamic acid (TXA) in trauma patients with evidence of hyperfibrinolysis (HF) on admission. The purpose of this study was to examine whether the use of TXA in patients with HF determined by admission rapid thrombelastography was associated with improved survival. METHODS Following institutional review board approval, we evaluated all trauma patients 16 years or older admitted between September 2009 and September 2013. HF was defined as LY-30 of 3% or greater. Patients with LY-30 less than 3.0% were excluded. Patients were divided into those who received TXA (TXA group) and those who did not (no-TXA group). After univariate analyses, a purposeful, logistic regression model was developed a priori to evaluate the impact of TXA on mortality (controlling for age, sex, Injury Severity Score (ISS), arrival physiology, and base deficit). RESULTS A total of 1, 032 patients met study criteria. Ninety-eight (10%) received TXA, and 934 (90%) did not. TXA patients were older (median age, 37 years vs. 32 years), were more severely injured (median ISS, 29 vs. 14), had a lower blood pressure (median systolic blood pressure 103 mm Hg vs. 125 mm Hg), and were more likely to be in shock (median, base excess, −5 mmol/dL vs. -2 mmol/dL), all p < 0.05. Twenty-three percent of the patients had a repeat thrombelastography within 6 hours; 8.8% of the TXA patients had LY-30 of 3% or greater on repeat rapid thrombelastography (vs. 10.1% in the no-TXA group, p = 0.679). Unadjusted in-hospital mortality was higher in the TXA group (40% vs. 17%, p < 0.001). There were no differences in venous thromboembolism (3.3% vs. 3.8%). Logistic regression failed to find a difference in in-hospital mortality among those receiving TXA (odds ratio, 0.74; 95% confidence interval, 0.38–1.40; p 0.80). CONCLUSION In the current study, the use of TXA was not associated with a reduction in mortality. Further studies are needed to better define who will benefit from an administration of TXA. LEVEL OF EVIDENCE Therapeutic study, level IV.